Benefits and Challenges of Distance Education for Students Pursuing an Electronic Engineering Degree in Latin America and the Caribbean During the Period 2020-2022: A Literature Review. (LACCEI, 2024)
Historically, changes that the educational system has been exposed to for a given discipline have been the result of an evolutionary process of knowledge and related techniques developed over years. Therefore, for immediate changes such as those caused by the COVID-19 pandemic, sectors such as Higher Education Institutions (HEIs) did not have the experience or technological structures that would allow them to continue operating in a traditional manner. Due to lockdowns, universities closed their doors and attempted to continue education remotely. Currently, the learning experiences obtained by students in these areas after the change to virtual modality are unknown. In this sense, the present review aims to understand the benefits and challenges of distance education for students pursuing an electronic engineering degree in Latin America and the Caribbean during the period 2020-2022. To achieve the stated objective, a narrative literature review was conducted using the Google Scholar database. The results of the electronic literature search allowed for a total of 294 articles to be obtained. Of these, a total of 4 were analyzed and discussed after meeting the inclusion criteria and research objective. The main challenges encountered were in the technological and academic domains, while the main benefits were in the social and academic domains. Therefore, understanding these documented experiences regarding distance education for electronic engineering students is important in order to establish a starting point that allows for the design of improvement strategies in response to this educational modality that is here to stay and has allowed us to experiment with a disruptive and full of opportunities educational model.